
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


\(5\dfrac{3}{4}:3+2\dfrac{1}{4}\times\dfrac{1}{3}-\dfrac{1}{8}=\left(5\dfrac{3}{4}+2\dfrac{1}{4}\right)\times\dfrac{1}{3}-\dfrac{1}{8}\\ =8\times\dfrac{1}{3}-\dfrac{1}{8}=\dfrac{8}{3}-\dfrac{1}{8}=\dfrac{61}{24}\\ ----\\ \dfrac{3}{5}:\dfrac{5}{6}:\dfrac{6}{7}:\dfrac{7}{8}+\dfrac{2}{5}+\dfrac{23}{35}\\ =\dfrac{3}{5}\times\dfrac{6}{5}\times\dfrac{7}{6}\times\dfrac{8}{7}+\dfrac{2}{5}+\dfrac{23}{35}=\dfrac{18}{25}\times\dfrac{4}{3}+\dfrac{2}{5}+\dfrac{23}{35}=\dfrac{353}{175}\)

5/6 nhân(2/3 cộng 1/3) cộng 5/3
5/6 nhân 1 cộng 5/3
5/6 cộng 5/3
5/2

a; 5\(\dfrac{3}{4}\) : 3 + 2\(\dfrac{1}{4}\).\(\dfrac{1}{3}\) - \(\dfrac{3}{8}\)
= \(\dfrac{23}{4}\) : 3 + \(\dfrac{9}{4}\).\(\dfrac{1}{3}\) - \(\dfrac{3}{8}\)
= \(\dfrac{23}{4}\) x \(\dfrac{1}{3}\) + \(\dfrac{3}{4}\) - \(\dfrac{3}{8}\)
= \(\dfrac{23}{12}\) + \(\dfrac{3}{4}\) - \(\dfrac{3}{8}\)
= \(\dfrac{46}{24}\) + \(\dfrac{18}{24}\) - \(\dfrac{9}{24}\)
= \(\dfrac{64}{24}\) - \(\dfrac{9}{24}\)
= \(\dfrac{55}{24}\)

\(\frac{3}{1\times2}+\frac{3}{2\times3}+...+\frac{3}{5\times6}\)
\(=3\left(\frac{1}{1\times2}+\frac{1}{2\times3}+...+\frac{1}{5\times6}\right)\)
\(=3\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{5}-\frac{1}{6}\right)\)
\(=3\left(1-\frac{1}{6}\right)=3\times\frac{5}{6}=\frac{5}{2}\)


Bn xem link này nè!
https://olm.vn/hoi-dap/detail/228355765413.html
#Hok_tốt
3/1*2 + 3/2*3 + 3/3*4 + 3/4*5 + 3/5*6
= 3 * ( 1/1*2 + 1/2*3 + 1/3*4 + 1/4*5 + 1/5*6 )
= 3 * (1/1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + 1/5 - 1/5 - 1/6)
= 3 * (1/1 - 1/6)
= 3 * 5/6
= 5/2
HOK TỐT